Isolation and identification of microorganisms present in 53 dogs suffering otitis externa - Fernández, Gibson; Barboza, Glen; Villalobos, Amri; Parra, Omaira; Finol, Geovanny; Ramírez, Roger (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Otitis externa is a multi-factorial etiology disease commonly affecting canines. It represents a complex pathology associated to infections caused by bacteria and yeasts, many times not responding to treatments. The goal of this study was to isolate and identify the pathogenic and non-pathogenic micro-organisms existent in otitis externa patients. This research was performed on 53 canine patients which were attended at the Outpatient Consult Service of the University Veterinary Policlinic at Zulia State University (UVP), and which showed clinical signs such as: auditory canal erythema, increased secretion, pain, continuous head shaking and pruritus, purulent secretions and pruritus being the most frequent. Samples were recollected from auditory canal horizontal portion exudates. Different bacteria groups were isolated in culture media, the most frequent were Pseudomona aeruginosa (22.22%), Proteus mirabilis (13.89%), Staphylococcus aureus (12.50%), Staphylococcus epidermidis (8.33%), Escherichia coli (5.56%) and Staphylococcus coagulase-negative (5.56%). In the control group, Bacillus spp. (16.67%), Staphylococcus epidermidis (16.67%) and Staphylococcus coagulase-negative (16.67%) were the most frequently isolated. Cytological examination showed Malassezia pachydermatis to be present in 69.8% of the cases studied. The most affected breeds were Poodles (30.19%), Mongrels (26.42%), Cocker Spaniels (16.98%) and German Shepherd Dogs (9.49%); likewise, a higher incidence of otitis was evidenced in dogs between 2 and 5 months of age (43.40%).